(untitled) (Research, Society and Development, 2022)
Thyroid neoplasms are the main types of endocrine malignancy, their incidence increasing in recent years. Routine diagnosis may present inconclusive results, leading to the need for using additional techniques that are more precise, such as molecular analysis. Therefore, it is essential to search for molecular markers for the diagnosis of these malignancies and their different histological types. The objective of this study was to identify diagnostic molecular markers for papillary thyroid carcinomas (PTC) and goiter lesions. For this, expression of genes belonging to the MAPK/KINASE pathway was assessed by the RT-qPCR technique. Additionally, complete biochemical profiles of the samples were obtained using Fourier transform infrared spectroscopy (FTIR). Results of RT-qPCR suggest that FOS, JUN, MAP2K6, CCNA1, SFN genes have the potential to be tumor markers of thyroid lesions, and the MAP2K6, CCNA1, SFN genes further have the potential to distinguish PTC samples from other thyroid lesions. FTIR results showed that PTC lesions can be distinguished from normal and benign tissues with 95.83% efficiency; changes in nucleic acids being the major classifying factor. Overall, results suggest potential of molecular and FTIR analysis in diagnosis of thyroid cancer.